Regression mathematical modeling of the population of mouse-like rodents, hosts of blood-sucking arthropods in the Non-Black Earth Zone by the example of the Kaluga Region - F. I. Vasilevich; A. M. Nikanorova; V. V. Kalmykov; A. I. Selyutina (Российский паразитологический журнал, 2021)
The purpose of the research is a regression mathematical modeling of the population of small mammals, hosts of ixodid ticks in the Kaluga Region, which allows assessing the likelihood of zoonotic and vector-borne diseases.Materials and methods. For 10 years (from 2009 to 2019), a 2k multifactorial experiment was performed in the field by the method of V. V. Kalmykov (2016). The study object was mouse-like rodents that are the most common in the Kaluga Region. Rodents were counted by standard methods using techniques of V. N. Shnitnikov (1929), P. B. Yurgenson (1934) and A. N. Formozov (1937). The generally accepted steel spring traps were used. Animals were counted throughout all habitats.Results and discussion. Regression mathematical models of the mouse-like rodent population were obtained depending on the average monthly temperature, precipitation and atmospheric pressure for the year in the Non-Black Earth Zone by the example of the Kaluga Region. The specific nature of the obtained analytical model is that the greatest influence on the population of small mammals is made by the interaction effect of two factors, temperature and atmospheric pressure. Their impact is more significant than the influence of each of the three study factors separately, in particular, it is stronger than the only influence of temperature by 1.02, the only impact of precipitation by 2.58, and the only impact of atmospheric pressure by 2.72. The analytic mathematical model allows us to calculate, without significant material or time costs, populations of mouse-like rodents not only in the Kaluga Region, but also in regions with similar climate conditions.